On a class of variational-hemivariational inequalities (2002)
In this paper we consider a class of variational-hemivariational inequalities. We use the critical point theory for nonsmooth functionals due to Motreanu-Panagiotopoulos [9]. We derive nontrivial solutions using the mountain-pass theorem.